Fintech Innovation: A Solution to Enhance the Sustainability of Micro, Small, and Medium Enterprises - Halawa, Forman; Gulo, Menliman Joyfal; Halawa, Borisman; Sinaga, Hizkia Edwar; Yunanda, Fayeno (Faatuatua Media Karya, 2025)
This research examines the role of Financial Technology (fintech) in the sustainability of Micro, Small, and Medium Enterprises (MSMEs). This topic is intriguing because fintech is rapidly evolving and holds significant potential to address the financing access challenges often faced by MSMEs. The research problem formulated is: What are the antecedents and consequences of fintech on the sustainability of MSMEs? This study provides new contributions by exploring the relationship between fintech adoption and MSME performance from the perspective of current literature, which has not been extensively researched. The method employed is a systematic literature review of 22 articles from the Scopus database that meet the inclusion criteria based on the keywords “Financial Technology” and “SMEs.” The results indicate that the antecedents of fintech adoption include financial literacy, perceived usefulness, regulatory support, and digital readiness, while the consequences encompass improved access to financing, operational efficiency, and business growth. Furthermore, it was found that challenges in using fintech include technological risks and a lack of explainability in AI methods. In conclusion, fintech plays a crucial role in supporting the sustainability of MSMEs through enhanced financial inclusion and market access. The implications of this research highlight the need for policies that support fintech adoption and improve financial literacy to strengthen the positive impact on MSMEs. This study proposes a future research agenda related to the development of more inclusive fintech business models and comparative studies between countries.